Code Switching in Twitter Jerome Polin: Sociolinguistics Study - Marelda Tri Hania Banowati; Hendar Hendar (Budapest International Research and Critics University, 2022)
This study aims to analyse and examine closely the types of code switching that occur in the Twitter account user Jerome Polin and the functions contained in each type. The method used in carrying out the study was a descriptive analysis method. The data used were taken from social media applications, namely Twitter user Jerome Polin. The results demonstrated that there are three types of Code Switching, namely Inter-sentential 2 (40%), Intra-sentential 2 (40%), and Tag Switching 1 (20%). Function of Code Switching on this research are bilingual 5 (31%), jokes 1 (6%), build solidarity 3 (19%), emphasize what is important 2 (12%), attracting attention 3 (19%), trend words 2 (13%).